Analisis Peran Kualitas Data dalam Membangun Kepercayaan dan Kepuasan Konsumen di E-Commerce - Nurul Hidayah; Hendestri Br Sembiring; Amelia Putri; Nurbaiti Nurbaiti (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The rapid development of e-commerce in Indonesia makes good data management very important. If the data presented is inaccurate or irrelevant, this can make consumers feel dissatisfied, and even lose trust in the platform. This study aims to see the extent to which data quality affects consumer trust and satisfaction on e-commerce platforms. The method used in this research is a literature study, namely by collecting and reviewing various scientific sources such as journals, books, and articles that discuss e-commerce, data quality, and consumer behavior. This study does not use field data, but focuses on the discussion of relevant previous studies. The results of the study show that good data quality such as accurate, complete, and appropriate data for consumer needs can increase user trust and satisfaction. Therefore, e-commerce platforms need to pay attention to good and transparent data management in order to maintain long-term relationships with their customers.